THE EFFECT OF NATIONAL ECONOMIC RECOVERY ON THE FINANCIAL PERFORMANCE DURING THE COVID-19 PANDEMIC - Aditya Restu Prabawa; Dyah Purwanti (Kesatuan Press, 2024)
The COVID-19 pandemic triggered a health crisis and ultimately had a broad impact on business. The slowdown in economic activity resulted in many businesses failing. In this crisis, the government's role is crucial in improving the economy. Based on the phenomenon, the study analyzes the impact of government roles and firm characteristics on financial performance during COVID-19. The sample is an Indonesian-listed company in the non-financial sector during 2020. Government intervention is proxied by National Economic Recovery (in Indonesia, known as Pemulihan Ekonomi Nasional-PEN) and firm characteristics by liquidity, efficiency, and market power. The study employed the difference-in-difference method to analyze the intervention and used ordinary least squares. National Economic Recovery is found inadequate to raise a firm's financial performance. Otherwise, efficiency and market power positively affect the firm financial performance. The study has some practical implications to execute. First, it is suggested that the government provide unemployment benefits equivalent to wage loss caused by the pandemic. Second, the firm must use its liquidity to adapt quickly to the environment since unused liquidity will be useless in the short term. Third, firms must also raise efficiency and market power to survive the pandemic.